Preliminary results of investigations of possible ground deformation structures in the early christian basilica, ancient Lechaion harbour, Corinth, Greece. - Minos-Minopoulos, D.; Pavlopoulos, K.; G., Apostolopoulos; Dominey-Howes, D.; Lekkas, E. (Bulletin of the Geological Society of Greece, 2013)
The Early Christian Basilica of Lechaion, Corinth, located on the western jetty of the ancient Lechaion harbour, was constructed during the late 5th century AD and archaeological excavations suggest that it was destroyed by seismic activity during 551-552 AD. Numerous depressions and buckling structures observed on the Basilica floor are indicative of ground deformation structures, likely associated with liquefaction. In an attempt to investigate the subsurface soil structure, and stratigraphy, a GPR survey and horizontal distribution of ground conductivity along ten selected transects was carried out, supplemented by stratigraphic data as described by archaeological trenches. The results of the study revealed subsurface deformation features providing sufficient indications that allow us to suggest that the surface structures observed on the Basilica floor are the surface expression of earthquake-induced ground liquefaction.